Comparative advertising between the conflicting priorities of fair competition, trademark holder's rights and consumer information under South African law compared to the European and German approach on this issue - Jungmann, Nina (Intellectual Property Research Unit, 2016)
The dissertation addresses the legal conflict which is related to the legitimacy of comparative advertising. The national legal system has the task to balance antagonistic interests of trademark proprietors, advertisers, consumers and the public at large. The thesis examines the South African, the European and the German legal system implemented a legal balance and presents consequences, commonalities and differences. After starting with an historical overview on comparative advertising in South Africa and the Advertising Standards Authorities' self-regulating system, the Common law of Unlawful Competition will be addressed with regard to its influences on comparative advertising. Further, the thesis deals with the South African Trade Mark Act and its interpretation of infringement in terms of comparative advertising. Also considering European jurisdiction will be considered. The European approach on trade marks and comparative advertising will be presented as it leads to the German approach on comparative advertising and served as inspiration for the South African Trade Marks Act. The manner of implementation of European Directives influencing comparative advertising in German national law will be examined. Hereby, the distinctive characteristics which are required for comparative advertising as well as the special statutory mentioned cases in which it is unlawful will be presented. The high level of legal differentiation shall be emphasized since this may lead to differences compared to the South African law. Finally, I will compare how South African law and German law approach the subject comparative advertising. Especially the influences of Common law and statutory law on unlawful competition will be compared and evaluated. It shall be presented which consequences can arise out of different systematic approaches in this field of law. Additionally, the differences in the legal approaches on trade mark infringement will be highlighted in respect of presenting whether they cause actual consequences for the final legal valuation of comparative advertising. Furthermore, the commonalities concerning the purpose of encouraging comparative advertising will be addressed.